Disparities in Effectiveness of Pneumococcal Vaccine in Industrialized and Developing Countries: Is Vaccination Closing the Gap? - R. Kornetsky; D. Greenberg; O. Falup-Pecurariu (Антибиотики и Химиотерапия, 2020)
Backgrounds Streptococcus pneumoniae cause serious disease including pneumonia, meningitis and bacteremia and mortality is seen most in developing countries. The aim of the study was to determine if the reduction in IPD and pneumonia rates were similar in developed and developing countries after the introduction of the pneumococcal conjugated vaccine and to determine changes in the disparities of these diseases rates in these countries. Methods. Literature searches were conducted by using the PubMed database and Google scholar. The main criterion for selection was that the studies compare incidence of IPD or pneumonia in children pre and post PCV7, PCV10, or PCV13 vaccine introduction. Only published articles that described the incidence rate of IPD or pneumonia with quantitative data were fully reviewed in detail. Results. A total of 22 articles were full-text original publications and one was a review article. Within 3 years of PCV introduction in the United States, all-cause IPD dropped from 98.7/100,000 to 20/100,000 children